Perancangan Sistem Pemantauan Pengendali Suhu pada Stirred Tank Heater menggunakan Supervisory Control and Data Acquisition (SCADA) - Ike Bayusari; Caroline .; Romli Septiadi; Bhakti Yudho Suprapto (Universitas Syiah Kuala, 2013)
This paper discusses design of a suhue control monitoring system in stirred tank heater system that has an important function in industrial processes. Monitoring of suhue control system in stirred tank heater is designed using Supervisory Control and Data Acquisition (SCADA) that control function of industrial processes. While the actuator to be controlled is the position of burner openings, so that the heat can be adjusted to meet a predetermined set-point. The suhue controller that is also used as a Remote Terminal Unit (RTU) is Programmable Logic Controller (PLC). The testing result showed on SCADA system was quite good, where the average percentage of deviation for testing of set-point data was 0.76687%, and the percentage of deviation for testing of suhue data was 0.082%.